EFL Learners' Learning and Retention of Phrasal Verbs and Lexical Collocations: Contributions from Formative Assessment - Zohreh Seifoori; Heidar Ahmadi (Journal of Modern Research in English Language Studies)
EFL learners’ difficulty in effectively learning and using phrasal verbs and lexical collocations might be attributed to the purely product-oriented teaching and assessment techniques used in public schools. This study aimed to investigate the impact of oral questions and written quizzes as two formative assessment (FA) techniques on Iranian learners’ learning and retention of phrasal verbs and lexical collocations. The research sample comprised 75 male intermediate EFL high school students, in Marand, East Azarbaijan, Iran, who were selected out of 90 grade four students based on their performance on a Nelson Proficiency test. The three intact classes, each with 25 participants, were randomly assigned as experimental group 1 (EG1) for whom we employed oral questions, experimental group 2 (EG2) who received written quizzes, and the control group (CG) with no process-oriented assessment. After the eight-week treatment, the one-way ANOVA analysis of the three sets of scores obtained from the pre-test, the immediate post-test, and the delayed post-test revealed that EG1 and EG2 outperformed the CG supporting the facilitative role of process-oriented assessment. The findings offer pedagogical implications with regard to FA that will be discussed.